2020
DOI: 10.3390/su12125167
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Assessing Soil Sealing in Padua Municipality through Biotope Area Factor Index

Abstract: Soil sealing is a worldwide phenomenon of covering of natural or seminatural soil with impervious surfaces, such as built-up or paved surfaces. It is widely recognized as a major environmental issue which drives landscape fragmentation and ecosystem services degradation and loss. Italy is one of European countries with the highest extent of soil sealing. The most affected area is northern Italy, especially the Po Valley with more than 12% of sealed surfaces. According to official data, Veneto Region and the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In urban landscapes, high spatial resolution is crucial to provide accurate urban cover classifications [29,32]. Urban cover assessment using high resolution imagery, in addition to offering a highly detailed map, allows the use of maps to drive urban transformations and to compare future scenarios [33]. Recently, the increasing accessibility of technologies led to a growing number of high spatial resolution (<3 m) experiments in urban contexts [7,29,32].…”
Section: Introductionmentioning
confidence: 99%
“…In urban landscapes, high spatial resolution is crucial to provide accurate urban cover classifications [29,32]. Urban cover assessment using high resolution imagery, in addition to offering a highly detailed map, allows the use of maps to drive urban transformations and to compare future scenarios [33]. Recently, the increasing accessibility of technologies led to a growing number of high spatial resolution (<3 m) experiments in urban contexts [7,29,32].…”
Section: Introductionmentioning
confidence: 99%
“…This is also confirmed by the mapping of the Biotope Area Factor Index, which expresses the share of ecologically effective area to total land area [57]. Nearly the entire industrial district is characterized by values equal to zero (i.e., totally impervious area) [53]. The study focused on a representative sector (Figure 1b), with the aim to evaluate the microclimatic impacts and potential benefits of the redevelopment of ground surfaces.…”
Section: Case Study Areamentioning
confidence: 84%
“…In cities, the major amplifier of climate risk factors is the expected intensification of extreme climate phenomena, especially heat waves and intense rainfalls. In this context, the Veneto region is among the areas in Italy most affected by soil sealing, with a share of more than 12% sealed surface [53] This results in several environmental issues, including the presence of urban heat island, and problems in stormwater management. A number of studies have confirmed the presence of UHI in Padua, especially during the summer seasons [51,[54][55][56].…”
Section: Geography and Climate Of Paduamentioning
confidence: 99%
“…Hereafter, we refer to vegetation indexes as Band Ratio class, by including NDVI, NDBI, MNDISI, SAVI, and others indexes (García and Pérez 2016, Sun et al 2017, Gong et al 2019, Zhong et al 2019). The reclassification process is referred to papers that used ancillary data, for example Land Cover data, to derive soil sealing coverage (Jennings et al 2004, Pristeri et al 2020. The image interpretation category includes scientific articles that adopted human visual analysis to identify and to map impervious areas (Hartcher andChowdhury 2017, Lozano et al 2019).…”
Section: Methodologies and Approaches To Mapping Soil Sealingmentioning
confidence: 99%